Mister Exam
Lang:
EN
EN
ES
RU
Other calculators
Integral Step by Step
Derivative Step by Step
Equation systems Step by Step
Identical expressions
-x*exp(-x/ two) + two *exp(-x/ two) = zero
minus x multiply by exponent of ( minus x divide by 2) plus 2 multiply by exponent of ( minus x divide by 2) equally 0
minus x multiply by exponent of ( minus x divide by two) plus two multiply by exponent of ( minus x divide by two) equally zero
-xexp(-x/2) + 2exp(-x/2) = 0
-xexp-x/2 + 2exp-x/2 = 0
-x*exp(-x divide by 2) + 2*exp(-x divide by 2) = 0
Similar expressions
-x*exp(-x/2) + 2*exp(x/2) = 0
-x*exp(x/2) + 2*exp(-x/2) = 0
-x*exp(-x/2) - 2*exp(-x/2) = 0
x*exp(-x/2) + 2*exp(-x/2) = 0
-x*exp(-x/2) + 2*exp(-x/2) = 0 equation
+ equation
Solve the equation!
The unknown in the equation:
v
Numerical solution:
Do search numerical solution at [
,
]